2021
DOI: 10.1029/2020jb020965
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Evolution of Induced Subduction Through the Inversion of Spreading Ridges

Abstract: • Dynamic evolution of ridgeinversed subduction affected by ridge structures and thermal states is investigated by 2D thermomechanical models • The cooling age of extinct spreading ridges and forced convergence rates play the dominant role in ridgeinversed subduction • Model results favor the scenario of ridge-inversed subduction of the Proto-South China Sea plate

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 53 publications
1
22
0
Order By: Relevance
“…This behaviour is tied to low convergence rates, i.e., below 0.9 cm yr-1 (Figure 8B). Similar results have been obtained by Gülcher et al (2019) and Qing et al (2021), who observed in their numerical models, reactivation of multiple detachment faults upon their inversion but did not produce intra-oceanic subduction. When deformation does not localized in oceanic domain, the vertical rheological decoupling at the margin allows for the development of a long-lasting shear zone where stresses are relaxed through the formation of a decollement that propagate through the mantle.…”
Section: Favourable Conditions For Subduction Initiation At Passive Marginssupporting
confidence: 89%
See 1 more Smart Citation
“…This behaviour is tied to low convergence rates, i.e., below 0.9 cm yr-1 (Figure 8B). Similar results have been obtained by Gülcher et al (2019) and Qing et al (2021), who observed in their numerical models, reactivation of multiple detachment faults upon their inversion but did not produce intra-oceanic subduction. When deformation does not localized in oceanic domain, the vertical rheological decoupling at the margin allows for the development of a long-lasting shear zone where stresses are relaxed through the formation of a decollement that propagate through the mantle.…”
Section: Favourable Conditions For Subduction Initiation At Passive Marginssupporting
confidence: 89%
“…Our results predict that even young (5 Myr old) oceanic lithospheres can support tectonic stress of up to 12 TN/m underlining its long-term stability. As such, subduction initiation along spreading ridges is largely favored by warm ridge and fast convergence rate (Figure 8C, see also Qing et al, 2021) and/or the implementation of lithosphere-scale pre-existing weak zones (Maffione et al, 2015) to localize deformation in the mantle lithosphere.…”
Section: Favourable Conditions For Subduction Initiation At Passive Marginsmentioning
confidence: 99%
“…Because a large age contrast across the transform fault is rare, the SSI model is unlikely to be widely applicable to SI on Earth. In contrast, the ISI model with young oceanic plates seem to explain the observations better (e.g., Keenan et al., 2016; Qing et al., 2021; Zhou & Wada, 2021). Geological observations indicate that some SI occurred at a transform boundary under transpression (Johnston et al., 2011; Lithgow‐Bertelloni & Guynn, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…The high geothermal gradient of metamorphic sole is not always the case during SI. Such a high-temperature condition at a shallow depth can hardly be obtained in other cases, including passive margins (e.g., Mueller & Phillips, 1991;Nikolaeva, et al, 2010;Zhong & Li, 2019, SI at a ceased spreading center/ridge for a long time (e.g., Qing et al, 2021), or the induced SI at transform fault/weak zone (e.g., Gurnis et al, 2019Gurnis et al, , 2004. For some of the SI at the southwest Pacific, the age of the overriding oceanic lithosphere during SI is generally over 10 Ma, which is too cold for the formation of metamorphic soles.…”
Section: The Ophiolite Without Metamorphic Solementioning
confidence: 99%